Gadolinium-based contrast agents aggravate mechanical and thermal hyperalgesia in a nitroglycerine-induced migraine model in male mice - Bilgin, Batuhan; Adam, Muhammed; Hekim, Munevver Gizem; Bulut, Ferah; Ozcan, Mete (Elsevier Science Inc, 2024)
In the diagnosis of migraine, which is a neurovascular disease, gadolinium-based contrast agents (GBCAs) are used to rule out more serious conditions. On the other hand, it remains unclear as a scientific gap whether GBCAs may trigger migraine-related pain. The aim of this study was to investigate the effect of GBCAs on mechanical and thermal pain behaviour in a nitroglycerin (NTG)-induced migraine model in mice. NTG (10 mg/kg) was administered intraperitoneally to adult (6-8 weeks old) BALB/c mice 2 h before behavioral tests 5 times every other day on days 1st, 3rd, 5th and 9th to induce migraine model (N = 50). As GBCAs, gadobenate dimeglumine (linear-ionic), Gadodiamide (linear-nonionic), and gadobutrol (macrocyclicnonionic) were delivered intravenously through the tail vein of mice for 5 days on test days. Mechanical pain threshold (plantar and facial withdrawal threshold) was evaluated by plantar von Frey and periorbital von Frey tests on days 1st, 5th, and 9th, and thermal pain threshold (latency) was evaluated by hot plate and cold plate tests on days 3rd and 7th. There was a statistically significant increase in mechanical and thermal hyperalgesia in NTG administered groups compared to the control group. Gadodiamide, gadobutrol and gadobenate dimeglumine administration significantly decreased latency, paw and facial withdrawal threshold (0.18 +/- 0.05, 0.17 +/- 0.07, 0.16 +/- 0.09; 9th day values respectively) compared to NTG group (0.27 +/- 0.05). The results of this in vivo study show that GBCAs produce effects that may trigger migraine attacks in migraine. It is recommended that these effects be further investigated and supported by further clinical studies.
Keywords: Migraine; Contrast agents; Gadobenate dimeglumine; Gadolinium; Gadodiamide; Gadobutrol